Hanging as a Method of Suicide: Retrospective Analysis of Postmortem Cases (Journal of Armed Forces Medical College, Bangladesh, 2011)
This retrospective study was conducted on 145 postmortem cases of hanging victims at government medical college morgue over a period of two years. The objective of this study was to find out the pattern of hanging cases as a proper method of suicide and to evaluate the present situation of hanging in this capital city. Out of 145 cases, 41% were male and 51% were married. One hundred and one victims hanged themselves at night, while 44 at day time. In 72 victims, stomachs were found empty. Most (97%) of the bodies were recovered from inside the living rooms. Ninety seven percent had complete suspension. One hundred and forty two (98%) cases had ligature mark in neck. Thirty nine cases had fracture of hyoid bones, 27 cases had fracture of thyroid cartilages. Most of the victims (45%) were from the age group 20- 30 years. Dopatta (orna) was the commonest (35%) ligature material. Quarrel among husband and wife was the commonest (31%) cause of suicidal hanging. Hanging was observed as a frequently used method of suicide in Bangladesh. Key words: Hanging, suicide; post mortem DOI: 10.3329/jafmc.v6i2.7273JAFMC Bangladesh. Vol 6, No 2 (December) 2010 pp.37-39